Vibrational Properties of Vacancy in Na and K Using MEAM Potential (Communications in Computational Physics, 2018)
The modified embedded atom method (MEAM) with the universal form ofembedding function and a modified energy term along with the pair potential hasbeen employed to determine the potentials for alkali metals: Na, K, by fitting to theCauchy pressure (C12−C44)/2, shear constants Gv = (C11−C12+3C44)/5 and C44, thecohesive energy and the vacancy formation energy. The obtained potentials are usedto calculate the phonon dispersions of these metals. Using these calculated phononswe evaluate the local density of states of neighbours of vacancy using Green's functionmethod. The local density of states of neighbours of vacancy has been used to calculatemean square displacements of these atoms and formation entropy of vacancy. Thecalculated mean square displacements of both 1st and 2nd neighbours of vacancy arefound to be lower than that of host atom. The calculated phonon dispersions agree wellwith the experimental phonon dispersion curves and the calculated results of vacancyformation entropy compare well with the other available results.